Multicentric Hemangiopericytoma of Posterior Fossa: A Rare Case and Review of Literature - Naik, Harish; Vernon, Velho; Bhide, Anuj; Guha, Amrita; Bhople, Laxmikant; Jain, Nimesh (Indian Journal of Neurosurgery, 2017)
Intracranial hemangiopericytoma is unusual, and those occurring in the posterior fossa are extremely rare. Surgery followed by radiotherapy is the mainstay of treatment. These tumors are known to recur locally and distant metastases are reported. Multicentricity either in the primary setting or in recurrent setting is rarely reported. We report here a rare case of multicentric posterior fossa hemangiopericytoma occurring in a 38-year-old man at two different intervals. The patient underwent total excision of right tentorial hemangiopericytoma in 2013, followed by radiotherapy. After being free from disease for 3 years, he developed a similar lesion on left tentorial leaflet in 2016 for which a total excision was once again done followed by adjuvant radiotherapy.
Keywords: hemangiopericytoma; surgery; radiotherapy